Financial Risk and Cost Stickiness: Evidence From Egypt - Mandour, Mohamed (International Journal of Accounting and Financial Reporting, 2021)
This study seeks to investigate whether the cost of goods sold (COGS) behaves asymmetric to change in sales, and examines the effect of financial risk on asymmetric cost behavior of COGS in the Egyptian manufacturing firms. The financial data of this study were collected from the published annual reports for a sample of 65 Egyptian listed manufacturing firms during the period (2006-2015) with total observations 530 firm-year. The analysis of this paper is based on Anderson et al.’s (2003) cost stickiness model. The findings indicate that the COGS is sticky to change in sales, it rises more when sales increase than when it falls for equivalent sales decrease and the degree of cost stickiness increases with a firm’s financial risk. This study is the first attempt to examine the direct effect of financial risk on the COGS behavior using Altman Z-score model as a proxy for financial risk, which may affect the accuracy of the results. By focusing on this proxy, the study identifies a significant relationship, which was not adequately addressed in previous studies. Therefore, this study extends the cost behavior literature by examining the impact of financial risk on managers' decisions to amend the resources.